Introducing Ten to Men, the Australian longitudinal study on male health. (October 2016) - Pirkis, Jane; Macdonald, John; English, Dallas
Abstract We are very pleased to introduce Ten to Men, the Australian Longitudinal Study on Male Health. Ten to Men is, to our knowledge, the largest national all-male cohort study in the world. It involves 15, 988 males who were aged between 10 and 55 years when we recruited them in 2013/14. Together, the articles in this collection provide an overview of the study's methods, examples of some of the key questions it can answer, and guidance for researchers wishing to use it. Perhaps most importantly, the articles demonstrate the enormous potential Ten to Men has to make a real difference to our understanding of male health and the factors that influence it.